2007
DOI: 10.2169/internalmedicine.46.6433
|View full text |Cite
|
Sign up to set email alerts
|

Adult Langerhans Cell Histiocytosis with Independently Relapsing Lung and Liver Lesions That was Successfully Treated with Etoposide

Abstract: A 35-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 14 publications
(14 reference statements)
0
6
0
Order By: Relevance
“…Case reports (74,75) have suggested that this intervention alone may lead to marked improvement or resolution of the disease. However, relapse or worsening despite smoking cessation have also been described (76,77). Nevertheless, because of the high rate of PLCH-associated pulmonary malignancy, the established relationship between smoking and airflow obstruction and many other health benefits, smoking cessation is the most important step in the management of PLCH.…”
Section: Smoking Cessationmentioning
confidence: 99%
See 1 more Smart Citation
“…Case reports (74,75) have suggested that this intervention alone may lead to marked improvement or resolution of the disease. However, relapse or worsening despite smoking cessation have also been described (76,77). Nevertheless, because of the high rate of PLCH-associated pulmonary malignancy, the established relationship between smoking and airflow obstruction and many other health benefits, smoking cessation is the most important step in the management of PLCH.…”
Section: Smoking Cessationmentioning
confidence: 99%
“…Most of the data on these agents come from studies in children showing improvement or remission of multisystem LCH (14,(79)(80)(81). Nevertheless, small case reports and case series (77,80,(82)(83)(84)(85)(86) suggest that these agents may have a role in the treatment of LCH with multisystem involvement in adults, including pulmonary disease, although lung-specific indexes of improvement vary.…”
Section: Cytotoxic Drugsmentioning
confidence: 99%
“…First, haematological disorders (leukaemia or lymphoma) may be associated with LCH, including adult PLCH [ 11 , 22 , 23 ], and they may thus be screened using these blood tests. Second, although it was not the case in our cohort, liver LCH involvement in adult PLCH patients has been reported [ 24 26 ]. Finally, the presence of lymphopaenia and biological liver alterations is important to consider in patients who will eventually need treatment for their disease.…”
Section: Discussionmentioning
confidence: 66%
“…Literature addressing the management of refractory/relapsed MS-LCH in adults is much less robust, most consisting of case reports (Table 2) [12,[23][24][25][26][27]. More recently, B-RAF mutations have been observed in 38% to 69% of cases of LCH [27], making salvage with vemurafenib an appropriate choice in patients that harbor the mutation.…”
Section: Discussionmentioning
confidence: 99%